Destinasi Wisata Ilmiah: Pelatihan Penulisan Artikel Ilmiah Melalui Metode Coaching Clinic - Siti Rahmah (Gunung Djati Conference Series, 2023)
This training aims to improve participants' scientific article writing skills and provide an in-depth understanding of the effective writing process. The coaching clinic method provides an opportunity for participants to refine and improve their writing skills through guidance and feedback provided by the facilitators. The training method involved a series of activities such as material delivery, group discussion, self review, self healing, self reflection, article consultation, and paper submission practice. The results and discussion showed that participants experienced significant improvement in their scientific article writing skills after attending this training. This training contributed greatly to the development of participants' research and scientific communication skills